2021
DOI: 10.1007/s10461-020-03154-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Risk of Human Immunodeficiency Virus (HIV) Virologic Failure in the Era of Undetectable Equals Untransmittable

Abstract: The “Undetectable = Untransmittable” campaign indicates that persons living with Human Immunodeficiency Virus (HIV) who maintain a suppressed viral load cannot sexually transmit the virus. However, there is little knowledge of the percent of individuals at a population level who sustain viral suppression long term. The aims of this study were to: (1) establish a baseline of persons living with diagnosed HIV who resided in New York and had consecutive suppressed viral load tests; (2) describe the risk of virolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, however, SSA participants represented 71.4% of those who experienced loss of virological suppression despite this subgroup representing only 32.3% of the overall cohort. Indeed, it has been reported that SSA people living with HIV were at higher risk of loss of virological suppression than non‐SSA people with HIV [26]. Of the 14 participants experiencing loss of virological suppression, six did not have resistance data available at the time of loss of virological suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, SSA participants represented 71.4% of those who experienced loss of virological suppression despite this subgroup representing only 32.3% of the overall cohort. Indeed, it has been reported that SSA people living with HIV were at higher risk of loss of virological suppression than non‐SSA people with HIV [26]. Of the 14 participants experiencing loss of virological suppression, six did not have resistance data available at the time of loss of virological suppression.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 17 , 18 However, established HIV-diagnosed individuals diagnosed for more than 6 months may also not disclose their serostatus and encourage their sexual partners to test for HIV due to potential social discrimination. 19 , 20 Compared with newly HIV-diagnosed individuals, adherence to ART during a long time in established HIV-diagnosed individuals is not always satisfactory, 21 , 22 , 23 and unprotected sexual behaviours may exist more frequently for the concept of “undetectable equals untransmittable”. 24 When HIV-diagnosed individuals are not in care or in care but viraemic, the sexual partners of these HIV-diagnosed individuals are also at potential risk for HIV acquisition and need HIV testing service.…”
Section: Introductionmentioning
confidence: 99%
“…Data from high-income countries show a need for ongoing VL monitoring even after achieving viral suppression. Laprise et al studied the long-term effect of persistent low-level viremia among a cohort of PWH, while Gunn et al showed that a third of participants experienced virologic failure despite attaining sustained viral suppression [ 17 , 18 ]. However, there are limited data on the outcome of clients who attain undetectable VL levels in low- and middle-income countries.…”
mentioning
confidence: 99%